Factors influencing recovery from mild traumatic brain injury. (28th July 2020) - Johnson, Leslie Weaver; Lundgren, Kristine; Henrich, Vincent; Phillips, Susan
ABSTRACT: Primary Objective: This study determined whether initial GCS score, head CT results, cognitive performance on IMPACT testing, or APOE genotype most effectively predicted 1-month functional outcome after mild traumatic brain injury (mTBI). This study tested the hypotheses that participants with poor performance on initial cognitive testing and those with an APOEe4 genotype would exhibit a poorer 1-month recovery after mTBI. Research Design: Regression analysis determined which independent variables were most effective in predicting 1-month GOS-E or DRS score. Independent t-test procedures determined whether cognitive recovery varied across APOEe4 carriers. Methods and Procedures: 49 participants admitted to the hospital with mTBI received cognitive evaluation within 48 hours after injury and again one month later. DNA analysis provided participant APOE genotype. Main Outcomes and Results: Results showed that no study variables significantly predicted GOS-E or DRS scores, however, differences were identified when APOE groups were compared. Participants who were noncarriers of APOEe4 had significantly slower reaction times compared to APOEe4 carriers. Participants who were homozygous APOEe4 carriers had significantly lower instances of impulsivity than noncarriers. Conclusions: Further research is needed to understand how APOE allele status and performance on initial cognitive testing may influence short-term recovery after mTBI.